Measuremet of Principal Parameters of Oxidative Stress in Blood Serum, Uterine and Placental Tissues of Pregnant Cats / Sanan Raza; Supervisor Nilgün Gültekin - Raza, Sanan (Ondokuz Mayıs Üniversitesi, Sağlık Bilimleri Enstitüsü, 2017)
…
Tez (yüksek lisans) -- Ondokuz Mayıs Üniversitesi, 2017
Libra Kayıt No: 119164
Keywords: Oksidatif Stres; Kediler -- Üreme; TEZ YÜK LİS S194m 2017